More Severe COVID-19 in Patients With Active Cancer: Results of a Multicenter Cohort Study - Monari, Caterina; Sagnelli, Caterina; Maggi, Paolo; Sangiovanni, Vincenzo; Numis, Fabio Giuliano; Gentile, Ivan; Masullo, Alfonso; Rescigno, Carolina; Calabria, Giosuele; Megna, Angelo Salomone; Gambardella, Michele; Manzillo, Elio; et al. (Frontiers in Oncology, 2021)
Background: The aim of the study was to compare coronavirus disease 2019 (COVID-19) severity presentation between oncologic and non-oncologic patients and to evaluate the impact of cancer type and stage on COVID-19 course. Methods: We performed a multicentre, retrospective study involving 13 COVID-19 Units in Campania region from February to May 2020. We defined as severe COVID-19 presentation the cases that required mechanical ventilation and/or admission to Intensive Care Units (ICU) and/or in case of death. Results: We enrolled 371 COVID-19 patients, of whom 34 (9.2%) had a history or a diagnosis of cancer (24 solid, 6 onco-hematological). Oncologic patients were older (p<0.001), had more comorbidities (p<0.001) and showed a higher rate of severe COVID-19 presentation (p=0.001) and of death (p<0.001). Compared to 12 patients with non-active cancer and to 337 without cancer, the 17 patients with active cancer had more comorbidities and showed a higher rate of severe COVID-19 and of mortality (all p values <0.001). Compared to the 281 non-severe patients, the 90 subjects with a severe presentation of COVID-19 were older (p<0.01), with more comorbidities (p<0.001) and with a higher rate of cancer (p=0.001). At multivariate analysis, age (OR 1.08, 95% CI: 1.04-1.11) and suffering from cancer in an active stage (OR 5.33, 95% CI: 1.77-16.53) were independently associated with severe COVID-19. Conclusions: Since the higher risk of severe evolution of COVID-19, cancer patients, especially those with an active malignancy, should be candidates for early evaluation of symptoms and early treatment for COVID-19.